2020
DOI: 10.1111/cas.14297
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of chemical probes that suppress Wnt/β‐catenin signaling through high‐throughput screening

Abstract: Aberrant activation of the Wnt/β‐catenin signaling pathway has been observed in a wide range of human tumors. Deregulation of the pathway is closely linked to various aspects of human carcinogenesis such as cell viability, regulation of cell cycle, epithelial‐mesenchymal transition, and maintenance of stemness. In addition, recent studies have disclosed the involvement of Wnt signaling in immune evasion of tumor cells. The accumulation of β‐catenin in the nucleus is a common feature of cancer cells carrying de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Here, we found that the phosphorylation of GSK3β at Ser9 was downregulated, whereas the phosphorylation of GSK3β at Tyr216 was upregulated in mortalin knockdown cells, which inhibited the phosphorylation of β-catenin at several main sites, such as Ser37, Thr41, and Tyr654. This downregulation of phosphorylation could inhibit β-catenin separation from the cell membrane, preventing it from entering the nucleus and performing its function and promoting the progression of cancer ( 44 , 45 ). In addition, the downstream apoptosis process-related genes, such as Bcl-XL, Bcl-2, and BAD, were also affected and induced the apoptosis process, consistent with their functions ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that the phosphorylation of GSK3β at Ser9 was downregulated, whereas the phosphorylation of GSK3β at Tyr216 was upregulated in mortalin knockdown cells, which inhibited the phosphorylation of β-catenin at several main sites, such as Ser37, Thr41, and Tyr654. This downregulation of phosphorylation could inhibit β-catenin separation from the cell membrane, preventing it from entering the nucleus and performing its function and promoting the progression of cancer ( 44 , 45 ). In addition, the downstream apoptosis process-related genes, such as Bcl-XL, Bcl-2, and BAD, were also affected and induced the apoptosis process, consistent with their functions ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…A series of small molecule inhibitors speci cally target several of the proteins in the Wnt signaling pathway, such as Fzd, DVL, PORCN or Tankyrase, and could also be used as chemical probes to dissect the mechanism(s) of these signaling pathways (37,38). We therefore used Wnt-C59, a PORCN inhibitor, in embryonic hippocampal neurons, to research polarization, the development of dendritic trees, and maintenance and/or maturation of dendritic spines; these inhibitory molecules have the potential to be developed both as study reagents in cell biology as therapeutic agents (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…A series of small molecule inhibitors speci cally target several of the proteins in the Wnt signaling pathway, such as Fzd, DVL, PORCN or Tankyrase, and could also be used as chemical probes to dissect the mechanism(s) of these signaling pathways (37,38). We therefore used Wnt-C59, a PORCN inhibitor, in young hippocampal neurons, to research polarization, the development of dendritic trees, and maintenance and/or maturation of dendritic spines; these inhibitory molecules have the potential to be developed both as study reagents in cell biology as therapeutic agents (39,40).…”
Section: Discussionmentioning
confidence: 99%